Ecosystem functioning and ecological status in the Venice lagoon, which relationships?. (December 2021) - Anelli Monti, M.; Brigolin, D.; Franzoi, P.; Libralato, S.; Pastres, R.; Solidoro, C.; Zucchetta, M.; Pranovi, F.
Highlights: An explicit spatial food web model for the Venice lagoon ecosystem is proposed. First attempt to move towards a food web model useful as supporting decision tool. Are the Biological Quality Elements of Water Framework Directive able to catch changes in ecological processes? Food web models as as tools for the WFD implementation in highly heterogeneous systems. Abstract: The implementation of management measures for improving the ecological status within an Ecosystem Based Management approach represents one the of the main challenges in coastal and transitional water environments. In general terms, ecological status and ecosystem functioning are expected to be positively associated, being good ecological processes a sort of prerequisite for the ecosystem health, but often relationships between ecosystem functioning indicators and the metrics used to define ecological status resulted to be rather puzzling. Moreover, the Biological Quality Elements (BQEs) do not show a consistent response to the changes in the ecosystem. This situation does not allow to recognize where interventions are really needed, hindering the definition of effective management strategies. In the present paper, a spatially explicit food web model of the Venice lagoon (with the resolution of 300 m) is used to simulate changes in the ecological status and related them to different management scenarios. Functional changes in the food web were investigated by comparing values of a set of 12 indicators derived by the ecological network analysis. In general, results highlighted on one hand the need for more discussion about the implementation of the WFD, at least in complex and spatially heterogeneous transitional waters environments, as the Venice lagoon; on the other, results remark the opportunity to support the BQEs monitoring with an ecological modelling approach. These models are certainly not the panacea for addressing questions about the environmental management, as they have inherent uncertainties (on parameters, structure, processes etc.); however, they can prove useful for selecting among different policy choices, since they offer the opportunity to simulate the mean effects, preliminarily verifying the efficacy of the proposed interventions.